COMPARATIVE ANALYSIS OF E-SYSTEM EFFECTIVENESS IN TAX REVENUE BEFORE AND DURING THE COVID-19 PANDEMIC (Case Study of KPP Pratama Jakarta Kebayoran Baru I) - Pinski Aulia Pradityani; Arni Karina; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This observation was designed to examine the comparison of the effectiveness of the E-System before and during the Covid 19 pandemic on tax revenues at KPP Kebayoran Baru I. The COVID-19 pandemic has had a broad impact on various sectors, as well as tax revenues in Indonesia. During the Covid-19 pandemic, social restrictions were enforced and people were required to comply with health protocols. In the midst of the Covid-19 pandemic situation, taxpayers must continue to carry out their tax obligations. This study used descriptive qualitative method. The data used in this observation is secondary data from KPP Kebayoran Baru I. The object of this research is KPP Kebayoran Baru I which is located in South Jakarta City. The researcher conducted an internship to obtain the required data, such as E-Registration, E-Filling, E-Billing data at KPP Kebayoran Baru I. The results of the research showed that there was an increase in NPWP registration and an increase in tax revenue. This proves that E-Registration and E-Billing are effective, so there is an increase. This increase in NPWP registration occurred due to the need for work requirements. And tax revenues increased because economic conditions during the Covid-19 pandemic were still stable. However, the other thing is that E-Filling is still not effective due to the limitations of the system used.